2019
DOI: 10.13189/ujer.2019.070509
|View full text |Cite
|
Sign up to set email alerts
|

Analysing E-tutoring Strategies to Foster Pre-service Language Teachers' Reflective Practice in the First Stages of Building an E-portfolio

Abstract: This study aims to analyse the tutoring strategies that three e-tutors employed in online written interactions with two of their corresponding pre-service teachers in the first stages of the development of their e-portfolio within a master's degree in online language teaching. Building on the data collected from thirty-four documents, which include the written drafts of the initial document of their e-portfolios (the Starting Point), the final versions of this document and their email exchanges, and the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…Similarly, different researchers emphasized the positive sides of the blog environment (Aschenbrenner & Miksch, 2005;Cuhadar & Kuzu, 2010;Deed & Edwards, 2011;Franklin-Matkowski, 2007;Hall & Davison, 2007;Jones, 2006;McGlinn-Manfra & Lee, 2012;Novillo & Pujola, 2019;Rahmi & Darmawan, 2018); in Jones (2006) research, it was found that there were superior aspects such as easy accessibility of activities in the blog environment, text and visual presentation in web page format, providing a critical or noncritical multi-point of view for feedback, providing an easy layout for publication and reading, no face-to-face communication for peer comments, providing awareness of the fact that the articles were being followed, presenting a solid audience and having content in relation to taking responsibility. Franklin-Matkowski (2007) also found that participants working in the blog environment valued collaboration and felt that the use of blogs improved their thinking skills by achieving higher levels of socialism and comprehension.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Similarly, different researchers emphasized the positive sides of the blog environment (Aschenbrenner & Miksch, 2005;Cuhadar & Kuzu, 2010;Deed & Edwards, 2011;Franklin-Matkowski, 2007;Hall & Davison, 2007;Jones, 2006;McGlinn-Manfra & Lee, 2012;Novillo & Pujola, 2019;Rahmi & Darmawan, 2018); in Jones (2006) research, it was found that there were superior aspects such as easy accessibility of activities in the blog environment, text and visual presentation in web page format, providing a critical or noncritical multi-point of view for feedback, providing an easy layout for publication and reading, no face-to-face communication for peer comments, providing awareness of the fact that the articles were being followed, presenting a solid audience and having content in relation to taking responsibility. Franklin-Matkowski (2007) also found that participants working in the blog environment valued collaboration and felt that the use of blogs improved their thinking skills by achieving higher levels of socialism and comprehension.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Horri dagokionez, geure buruari galdetu behar diogu zer-nolako laguntzari eta "estimulazio" gogoetatsuari eman nahi diogun bide: nori jakinarazi nahi diogun geure irakaskuntza-garapena eta norekin aritu nahi dugun "solasean" gogoeta egiteko. Hasierako prestakuntzako portfolio bat egitean, prestatzen ari diren irakasleek tutore edo mentore baten laguntza jaso dezakete etengabe (Pueyo, 2016;Novillo & Pujolà, 2019), edo elkarrekin bideratutako gogoeta sustatzen duten laguntza emateko beste modu batzuk, irakasleekin eta berdinekin, ekintza espezifikoetatik abiatuta, hala nola microteaching delakoa edo ikasgelako behaketa (Batlle et al, 2019;Cuesta et al, prentsan). Bestalde, jarduneko irakasleen kasuan, portfolioa egitearekin batera, teacher critical friendships edo irakasle-bikote kritikoak bidera daitezke (Farrell, 2007).…”
Section: Azahara Cuesta García Mª Vicenta González Argüello Eta Joan-...unclassified